Research Teaching and Training in Demography : . A Directory of Institutions in the ECAFE Region - United Nations Economic and Social Commission for Asia and the Pacific, Bangkok (Thailand).; United Nations Economic and Social Commission for Asia and the Pacific, Bangkok (Thailand). ([Washington : Distributed by ERIC Clearinghouse, 1974)
This comprehensive directory of research, teaching and training institutions in demography in the region of the Economic Commission for Asia and the Far East (ECAFE) represents the fulfillment of a major recommendation of the First Asian Population Conference of 1963. It shows existing diversity of institutions in 20 countries, facilitating direct contacts between staff and helping planners and policy-makers utilize and develop research. Classified alphabetically by country, each institution (210 total) lists its name, address, person in charge and official title, first year of research/teaching in demography, professional staff, research projects, curricula, and publications. Entries for professional staff include the person's sex, year of birth, subject profession, main courses taught, mother tongue, and other languages known. Research projects define project title, director(s), date of completion, aim and area of research. Works published as direct products of the research follow each project. Notes for curricula indicate the existence of an international exchange program or desire to establish one, language(s) used for teaching demography, entrance requirements, diploma offered, and courses of demographic interest together with their estimated number of hours. Appended material compiles sample questionnaires and indexes to institutions, areas of research, and people covered. (BL)
ERIC Note: Asian Population Studies Series No. 8.
Microfiche.
Keywords: Curriculum; Demography; Directories; Foreign Countries; Institutions; Population Education; Professional Personnel; Research; Teaching; Training; Asia -- Far East